2019
DOI: 10.1039/c9qm00257j
|View full text |Cite
|
Sign up to set email alerts
|

BODIPY@carbon dot nanocomposites for enhanced photodynamic activity

Abstract: BODIPY@carbon dot nanocomposites were made, which improved the solubility of BODIPY and enhanced the photodynamic activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 43 publications
0
31
0
Order By: Relevance
“…The nanocomposite exhibited high water solubility, good biocompatibility, and photodynamic therapy efficiency. 30 Many research efforts have attempted to build Cdot-based FRET systems as nanoprobes. Fig.…”
Section: Kang Liangmentioning
confidence: 99%
“…The nanocomposite exhibited high water solubility, good biocompatibility, and photodynamic therapy efficiency. 30 Many research efforts have attempted to build Cdot-based FRET systems as nanoprobes. Fig.…”
Section: Kang Liangmentioning
confidence: 99%
“…Our group has developed several CDs based nanocomposites for cancer diagnosis and treatment. [ 30,43–48 ] Besides, Jelinek et al synthesized self‐healing gels through cross‐linking reaction between CDs and polyethylenimine. [ 49 ] However, as far as we know, CDs‐based COFs have not been reported yet, although they are conceptually practicable.…”
Section: Introductionmentioning
confidence: 99%
“…These results showed that the obtained NPs possess good cytocompatibility and could be used for living cell imaging and effective PDT and shed light on one-pot synthesis of PEGylated fluorescent nanoparticles via multicomponent reaction for biomedical application [25]. Su et al [26] developed a strategy to fabricate a kind of nanocomposite (CBNPs) via the noncovalent interactions between Carbon Dots (CDs) and BODIPY, by which the solubility and PDT effects of BODIPY were improved through the Fluorescence Resonance Energy Transfer (FRET) mechanism. The CBNPs exhibit good water solubility, excellent singlet oxygen quantum yield, and high biocompatibility and PDT efficiency.…”
Section: Introductionmentioning
confidence: 87%
“…The CBNPs exhibit good water solubility, excellent singlet oxygen quantum yield, and high biocompatibility and PDT efficiency. They declared that these compounds may have potential applications in biomedical fields and cancer treatment [26].…”
Section: Introductionmentioning
confidence: 99%